Performance enhancement of a wideband spiral antenna using a stepped ground plane - Mohamad, Sarah Yasmin; Cahill, Robert; Fusco, Vincent (John Wiley, 2014)
This study presents the use of a stepped ground plane as a means to increase the gain and front-to-back ratio of an Archimedean spiral which operates in the frequency range 3–10 GHz. The backing structure is designed to optimize the antenna performance in discrete 1 GHz bands by placing each of the eight metal steps one quarter wavelength below the corresponding active regions of the spiral. Simulated and experimental results show that this type of ground plane can be designed to enhance the antenna performance over the entire 105% operating bandwidth of the spiral.